Moderasi Beragama Sebagai Strategi Perdamaian: Studi Kasus Gerakan Sosial Keagamaan Di Asia Tenggara - Oktavia Agata (CV. SINAR HOWUHOWU, 2025)
This article examines religious moderation as an effective peace strategy through a case study of religious social movements in Southeast Asia. Although religion is often a source of conflict, this research argues that inclusive interpretations and moderate practices can be powerful instruments for building social cohesion and peace. Using a qualitative approach with a case study strategy, data was collected through in-depth interviews, observation, and document analysis. The findings indicate that these movements successfully demonstrate religious moderation through the deconstruction of extremist narratives, community empowerment, authentic interfaith dialogue, and the use of art and culture. The study confirms that religious moderation is not merely a theological concept, but a tangible action operated at the grassroots level, supported by progressive leadership and active community participation. This research contributes to the literature by providing empirical evidence that a peace strategy based on religious values can significantly reduce tensions and create more harmonious societies in a highly diverse region.